Forest fragmentation on the national forest of irati bufferzone – Brazil - Winagraski, Etienne; Deus, Karina Henkel Proceke de; Marcelino, Vânia Rossetto; Oliveira Filho, Paulo Costa de (Ciência e Natura, 2018)
The National Forest of Irati is the Protected Area with the bigger surface of Ombrophyllous Mixed Forest (1.585,45 ha) in state of Paraná. If added to other forms of native vegetation associated with this ecosystem, as wetlands and brushwoods, is the largest protected area in Brazil (2.215,25 ha). The objective was the spatialization of the bufferzone (7 km) around Irati National Forest, in an approach to landscape ecology, through the analysis of the 2006 SPOT satellite image, 5 m resolution. In obtaining the metrics we used softwares Spring and Excel. The analysis result the identification of 47 forest fragments, 67 forest corridors and 189 stepping-stones. After the landscape indices calculated, we concluded that the area studied is less fragmented than the Araucaria Forest fragmentation pattern in South and Southeast of the country.